The Effect of Inspiratory Muscle Warm-Up on VO2 Kinetics during Submaximal Rowing - Mati Arend; Jana Kivastik; Jaak Talts; Jarek Mäestu (MDPI AG, 2021)
The aim of the study was to investigate the effect of an inspiratory muscle warm-up on the VO2 kinetics during submaximal intensity ergometer rowing. Ten competitive male rowers (age 23.1 ± 3.8 years; height 188.1 ± 6.3 cm; body mass 85.6 ± 6.6 kg) took part in this investigation. A submaximal constant intensity (90% PVO2max) rowing test to volitional exhaustion was carried out twice with the standard rowing warm-up (Test 1) and with the standard rowing warm-up with additional specific inspiratory muscle warm-up of two sets of 30 repetitions at 40% maximal inspiratory pressure (Test 2). We found a significant correlation between time constant (τ1) and the VO2 value at 400 s in Test 1 (r = 0.78; p < 0.05); however, no correlation was found between those parameters in Test 2. In addition, we found a positive association between VO2max from the incremental rowing test and τ1 from Test 1 (r = 0.71; p < 0.05), whereas VO2 did not correlate with τ1 from Test 2. Adding inspiratory muscle warm-up of 40% maximal inspiratory pressure to regular rowing warm-up had no significant effect on oxygen consumption kinetics during submaximal rowing tests.